Coexistence of superconductivity and complex 4 f magnetism in Eu0.5Ce0.5BiS2F. (8th September 2015) - Zhai, Hui-Fei; Zhang, Pan; Tang, Zhang-Tu; Bao, Jin-Ke; Jiang, Hao; Feng, Chun-Mu; Xu, Zhu-An; Cao, Guang-Han
Abstract: EuBiS2 F is a self-doped superconductor due to the mixed valence of Eu. Here we report that, with the Ce substitution for Eu by 50 at.%, the material exhibits ferromagnetic ordering at 8 K for the Ce-4  f moment, superconductivity at 2.2 K in the BiS2 layers and possibly antiferromagnetic ordering at 2.1 K for the Eu-4  f spins. The Eu valence is essentially divalent with the Ce incorporation. We tentatively interpret the coexistence of ferromagnetism and superconductivity by considering different Bi-6 p orbitals that are responsible for the superconductivity itself and for mediating the ferromagnetic interaction, respectively. We argue that the antiferromagnetic ordering of the Eu-4  f spins is most likely due to a magnetic dipole-dipole interaction.